Analisis Tingkat Kepuasan Konsumen dengan Metode Importance Performance Analysis (IPA) (Studi Kasus : Kedai Tujuh Gerobak) - Rusdianto, Andrew Setiawan; Amilia, Winda; Choiron, Miftahul; Suryadharma, Bertung; Wardhani, Dyah Ayu Kusuma (Jurnal Penelitian Sains dan Teknologi Indonesia, 2023)
Taking a case study at Kedai Tujuh Gerobak Denpasar as the object of research, Analysis used at Kedai Tujuh Gerobak Denpasar with the Importance Performance Analysis (IPA) method. The research stage was carried out by twice distributing questionnaires with a total of 30 respondents to conduct validity tests and reliability tests on twenty-nine attributes. Attributes that are in accordance with the validity test and reliability test will be distributed in the form of questionnaires to 100 respondents. The questionnaire will be used as a source of data as material for conducting science analysis (Importance Performance Analysis). The age characteristics of respondents ranged from 17 to 25 years as many as 47 people, ages between 26 to 34 years as many as 31 people and ages over 34 years as many as 22 people. The characteristics of respondents based on profession are known to students / students as many as 56 people, civil servants. TNI/POLRI as many as 13 people for self-employed as many as 24 people. Characteristics based on the frequency of purchases between 1 to 3 times as many as 33 people between 4 to 6 times as many as 29 people and consumers with a frequency of purchases more than 6 times as many as 38 people. The results of the consumer satisfaction level questionnaire or IKP of 86.67% indicate that the products offered are in accordance with customer expectations and the services provided are able to provide comfort for customers.